Auto-immunoproteomics analysis of COVID-19 ICU patients revealed increased levels of autoantibodies related to the male reproductive system - Schmidt, Frank; Abdesselem, Houari B.; Suhre, Karsten; Vaikath, Nishant N.; Sohail, Muhammad U.; Al-Nesf, Maryam; Bensmail, Ilham; Mashod, Fathima; Sarwath, Hina; Bernhardt, Joerg; Schaefer-Ramadan, Stephanie; Tan, Ti-Myen; et al. (Frontiers in Physiology, 2023)
Background: Coronavirus disease (COVID-19) manifests many clinical symptoms, including an exacerbated immune response and cytokine storm. Autoantibodies in COVID-19 may have severe prodromal effects that are poorly understood. The interaction between these autoantibodies and self-antigens can result in systemic inflammation and organ dysfunction. However, the role of autoantibodies in COVID-19 complications has yet to be fully understood. Methods: The current investigation screened two independent cohorts of 97 COVID-19 patients (Discovery (Disc) cohort from Qatar (case = 49 vs. control = 48) and Replication (Rep) cohort from New York (case = 48 vs control = 28)) utilizing high-throughput KoRectly Expressed (KREX) immunome protein-array technology. Total IgG autoantibody responses were evaluated against 1,318 correctly folded and full-length human proteins. Samples were randomly applied on the precoated microarray slides for 2 hours. Cy3-labeled secondary antibodies were used to detect IgG autoantibodies response. Slides were scanned at a fixed gain setting using the Agilent fluorescence microarray scanner, generating a 16-bit TIFF file. Group comparisons were made using a linear model and Fisher’s exact test. Differentially expressed proteins were used for KEGG- and WIKI-Pathways annotation to determine pathways in which the proteins of interest were significantly over-represented. Results and conclusions: Autoantibody responses to 57 proteins were significantly altered in the COVID-19 Disc cohort compared to healthy controls (P ≤ 0.05). The Rep cohort had altered autoantibody responses against 26 proteins compared to non-COVID-19 ICU patients that served as controls. Both cohorts showed substantial similarities (r2 = 0.73) and exhibited higher autoantibodies responses to numerous transcription factors, immunomodulatory proteins, and human disease markers. Analysis of the combined cohorts revealed elevated autoantibody responses against SPANXN4, STK25, ATF4, PRKD2, and CHMP3 proteins in COVID-19 patients. The sequences for SPANXN4 and STK25 were cross validated using sequence alignment tools. ELISA and Western blot further verified the autoantigen-autoantibody response of SPANXN4. SPANXN4 is essential for spermiogenesis and male fertility, which may predict a potential role for this protein in COVID-19 associated male reproductive tract complications and warrants further research.